(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today’s ubiquitous IT environment, even non-living objects interact with one another and intelligently respond to changing circumstances. The Internet of Things (IoT) is a new technology that recognises and conceptualises the essence of computers. The article provides a short overview of IoT-enabled water bottles. Water is an essential component of human existence. The quality of water is influenced by a number of factors. The smart water bottle with touch and photoplethysmographic sensors can accurately detect the quantity of liquid in the bottle, monitor activity with inertial sensors, and physiological characteristics with a touch and photoplethysmographic sensor.The smart bottle uses input sensors to continuously monitor these parameters in real time; the system then analyses the data and, if necessary, uses actuators to execute the appropriate actions. In today’s world, this method will be beneficial to health-conscious people. This method may also be very useful in the healthcare industry, where additional caution is required in all areas.